Between Day and Night : Deciphering the Nexus of Land Use and Property Crime in Malaysia’s Urban Territories - Azizul, Ahmad; Tarmiji, Masron; Mohamad Hardyman, Barawi; Syahrul Nizam, Junaini; Yoshinari, Kimura; Ruslan, Rainis; Mohd Azizul Hafiz, Jamian (Taylor & Francis Group, 2025)
Rapid urbanization in Malaysia has shaped a complex property crime landscape, especially in Selangor and Kuala Lumpur. This study examines the relationship between urban land use and property crime (2015–2020) using spatial analysis, particularly Getis-Ord Gi* hot spot analysis. By categorizing 12 land use types and analyzing four daily timeframes, it identifies crime-prone areas and temporal trends. Findings highlight land use influences on crime distribution, emphasizing the need for data-driven urban planning and policing strategies. Despite relying on secondary data, the study underscores the necessity of primary data collection and broader comparisons to enhance crime prevention policies.